Genoarchitecture of the Early Postmitotic Pretectum and the Role of Wnt Signaling in Shaping Pretectal Neurochemical Anatomy in Zebrafish - Brożko, Nikola; Baggio, Suelen; Lipiec, Marcin A.; Jankowska, Marta; Szewczyk, Łukasz M.; Gabriel, Michael O.; Chakraborty, Chaitali; Ferran, José L.; Wiśniewska, Marta B. (Frontiers in Neuroanatomy, 2022)
The pretectum has a distinct nuclear arrangement and complex neurochemical anatomy. While previous genoarchitectural studies have described rostrocaudal and dorsoventral progenitor domains and subdomains in different species, the relationship between this early partition and its later derivatives giving rise to the mature anatomy is less understood. The signals and transcription factors that control the establishment of pretectal anatomy are practically unknown. We investigated the possibility that some aspects of the development of pretectal divisions are controlled by Wnt signalling, focusing on the transitional stage between neurogenesis and histogenesis in zebrafish. Using several molecular markers and following the prosomeric model, we identified derivatives from each rostrocaudal progenitor pretectal domain and described the localization of gad1b-positive GABAergic and vglut2.2-positive glutamatergic cell clusters. We also attempted to relate these clusters to pretectal nuclei in the mature brain. Then, we examined the influence of Wnt signalling on the size of neurochemically distinctive pretectal areas, using a chemical inhibitor of the Wnt pathway and CRISPR/Cas9 approach to knock out genes that encode the Wnt pathway mediators, Lef1 and Tcf7l2. The downregulation of the Wnt pathway led to a decrease in two GABAergic clusters and an expansion of a glutamatergic subregion in the maturing pretectum. This revealed an instructive role of the Wnt signal in the development of the pretectum during neurogenesis. The molecular anatomy presented here improves our understanding of pretectal development during early postmitotic stages and support that Wnt signalling is involved in shaping the neurochemical organization of the pretectum.